2005
DOI: 10.1517/13543784.14.11.1419
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on gossypol: past and present developments

Abstract: Gossypol has received significant attention as a result of its potential therapeutic application as a male antifertility agent. Furthermore, recent research examining the biological activity of gossypol has revealed a number of other promising lines of enquiry. These have focused on the antitumour, antiviral and antioxidant actions of the compound in various disease states. This article provides an overview of the studies on the biological activity of gossypol, with particular attention paid to the mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
113
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 148 publications
(116 citation statements)
references
References 76 publications
0
113
0
3
Order By: Relevance
“…To test this possibility, we focused on gossypol, a bioavailable compound with BH3 functions, which had a safe profile in clinical trials. 23 Natural gossypol (a mixture of (À) and ( þ ) enantiomers) binds Mcl-1, Bcl-2 and Bcl-x L with IC 50 values of 1.74, 0.28 and 3.03 mM, respectively. 20 However, a number of reports have shown that of the two enantiomers, (À)-gossypol is significantly the most potent anticancer agent in vitro and in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To test this possibility, we focused on gossypol, a bioavailable compound with BH3 functions, which had a safe profile in clinical trials. 23 Natural gossypol (a mixture of (À) and ( þ ) enantiomers) binds Mcl-1, Bcl-2 and Bcl-x L with IC 50 values of 1.74, 0.28 and 3.03 mM, respectively. 20 However, a number of reports have shown that of the two enantiomers, (À)-gossypol is significantly the most potent anticancer agent in vitro and in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…20 However, a number of reports have shown that of the two enantiomers, (À)-gossypol is significantly the most potent anticancer agent in vitro and in vivo. 23 To estimate the binding affinities of (À)-gossypol for individual Bcl-2 family members, competition fluorescence polarization assays were performed with a fluorescently tagged Bid BH3 peptide. 24 K i values were determined instead of binding concentrations, as they more directly measure the inhibitory capacity of (À)-gossypol.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations